P050 'Food and Eating behaviour' – Development of a Guideline for Dutch Preventive Child Health Care. (15th August 2013) - Lanting, C; Heerdink-Obenhuijsen, N; Kamphuis, M
Abstract : Background: Many parents worry that their child is eating either too much or too little. In The Netherlands, Preventive Child Health Care (PCHC) is the main source of advice and information on food and eating behaviour. Yet, evidence on the subject is sparse and scattered. The Dutch Ministry of Health Welfare and Sports, therefore, requested a guideline; the PCHC-guideline should fit together with a guideline for paediatricians on the same subject, which was developed concurrently. Objectives: To develop a national guideline for PCHC-professionals on the subject to enhance uniform, evidence-based practice. Methods: A working group of guideline developers, epidemiologists, and dieticians, together with professionals in PCHC, child-psychology and -pedagogics, and a pre-speech therapist developed the guideline, according to the principles of evidence-based medicine. Close collaboration took place with a group of paediatricians developing the new guideline 'Signalling somatic causes of abnormal nutritional behaviour in children'. Questions were formulated by the working group and evidence was extracted from literature, supplemented by practice-based consensus. The guideline was piloted in several PCHC settings. Results: Together with a group of child psychologists and psychiatrists, referral criteria for eating disorders were agreed on. Paediatricians formulated 'Somatic alarm symptoms'. Discussion Working with a large, interdisciplinary group of guideline developers carries the risk of collaboration problems, but when managed successfully, adds value to the end product. Implications for Guideline Developers/Users: In order to avoid collaboration problems, the scope of the guideline was agreed on in an early stage. Interdisciplinary collaboration enhanced guideline quality.